Poster: A Case for Heterogenous Co-Simulation of Cooperative and Autonomous Driving - Hardes, Tobias; Turcanu, Ion; Sommer, Christoph (14th IEEE Vehicular Networking Conference (VNC 2023))
Many exciting future research topics in the field of Cooperative Autonomous Vehicles (CAVs) require the simulation of both connectivity and automation components. However, existing simulation tools focus on only one of these two aspects while making idealistic assumptions about the other. In this work, we motivate the use of established libraries such as gRPC to couple existing independent simulation tools tailored to either connectivity or automation, and demonstrate the feasibility of such an approach. We also describe an Open Source reference implementation coupling CARLA and Veins.

Design and Evaluation of an AR Voice-based Indoor UAV Assistant for Smart Home Scenarios - Helmert, Robin; Hardes, Tobias; Yigitbas, Enes (Proceedings of the ACM Symposium on Spatial User Interaction (SUI 2023))
As technology advances, Unmanned Aerial Vehicles ( UAVs) have emerged as an innovative solution to a variety of problems in many fields. Automated control of UAVs is most common in large area operations, but they may also increase the versatility of smart home compositions by acting as a physical helper. For example, a voice- controlled UAV could act as an intelligent aerial assistant that can be seamlessly integrated into smart home systems. In this paper, we present a novel Augmented Reality (AR )-based UAV control that provides high-level control over a UAV by automating common UAV missions. In our work, we enable users to operate a small UAV hands-free using only a small set of voice commands. To help users identify the targets, and to understand the UAV ’s intentions, targets within the user’s field of vision are highlighted in an AR interface. We evaluate our approach in a user study (n=26) regarding usability, physical and mental demand, as well as a focus on the users’ preferences. Our study showed that the use of the proposed control was not only accepted, but some users stated that they would use such a system at home to help with some tasks at home

Entwicklungsprädiktoren fachdidaktischen Wissens zu digitalen Medien - Schubatzky, Thomas; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Riese, Josef; Weiler, David (Lernen, Lehren und Forschen in einer digital geprägten Welt. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Aachen 2022)

Erste Ergebnisse eines Seminars zur Förderung digitaler Kompetenzen - Weiler, David; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Lachner, Andreas; Riese, Josef; Schubatzky, Thomas (Lernen, Lehren und Forschen in einer digital geprägten Welt. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Aachen 2022)

Entwicklung und Evaluation eines Fachpraktikums für das Lehramtsstudium Technik zur Förderung fachpraktischer Kompetenzen - Ermel, Dorothee Leonie
High-quality teacher education is the basis for high competences of future teachers. To prepare them adequately for the demands of their future teaching profession, it is essential to know (i) which subject-specific competences and skills they need and (ii) how these can be acquired in teacher education. However, empirical findings on necessary competences as well as on the design of teacher training courses are scarcely available on the subject of technology, since mainly general, normative recommendations on potential study contents exist. To fill this gap, this work focuses on the investigation of necessary practical competences of prospective technology teachers. The acquisition of such practical competences and skills is of great importance for the school subject of technology when, for example, machines are operated, tools are used, or objects are designed and manufactured. However, there is a lack of a differentiated description of the practical requirements for technology teachers and the teaching-learning processes required for this in the teacher training. The aim of this work is therefore the theory- and empirically-guided development and evaluation of a practical demand-oriented course for the technology teacher training programme at RWTH Aachen University to promote subject-specific practical competences. The development was structured as an iterative process by the Model of Educational Reconstruction (MER), according to which three major aspects were investigated and connected. (1) In a first step, the competences to be acquired were described and structured, taking normative perspectives into account as well as an empirical needs assessment among teachers and teacher educators to clarify and analyse the science subject matter. (2) In a second step, the student teacher´s perspective was surveyed to adapt the course to their initial competences, skills and experiences. (3) In a third step, the content and the didactic structure of the practical course was developed iteratively, considering the findings of the preceding steps and various requirements for the design and the tasks of the practical course (e.g., a necessary differentiation or a self-directed examination of the practical tasks in the course). The practical course was taught in several runs and evaluated with respect to the perceived learning outcomes of the student teachers as well as to the quality of the course. The evaluation was carried out through self-assessment of the students in a questionnaire and a written portfolio. The findings of the evaluation indicate a positive perception regarding the quality of the course. The students positively assessed the course structure (e.g., sequence of the course contents) and individual course elements (e.g., concrete course tasks). Furthermore, an increase in practical competences and skills – regardless of initial experience – was found. The work provides groundwork for further studies, for example on the level of competence acquisition or the long-term effect of the practical course.

Schreibimpulse in sprachlichen Lernprozessen - Drepper, Laura; Herrmann, Franziska; Nußbaum, Alena (Schreibunterricht. Studien und Diskurse zum Verschriften und Vertexten)

Rechtschreibfehler - Drepper, Laura (Wörterbücher zur Sprach- und Kommunikationswissenschaft (WSK) Online)

Rechtschreibanalyse - Drepper, Laura (Wörterbücher zur Sprach- und Kommunikationswissenschaft (WSK) Online)

Rechtschreibregel - Drepper, Laura (Wörterbücher zur Sprach- und Kommunikationswissenschaft (WSK))

Quellen und Flüsse in den Monumenta. Zum Natur- und Umweltbewusstsein eines Barockfürsten - Ströhmer, Michael (Monumenta. Erinnerungsorte zwischen Weser und Lippe. Die Monumenta Paderbornsensia des Ferdinand von Fürstenberg)

Leben an den Quellen. Europäische Wasserkultur entlang der Pader

'Pappeln, die grüne Messer sind' und 'ratlose Brillenbären in Zoo'. Deformierte Naturverhältnisse bei Angela Krauß und Herta Müller - Morrien, Rita (Werke im Dialog. (Virtuelle) Begegnungen anlässlich von 40 Jahren Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller)

Prekäre Existenzen - Geschlecht, Klasse, Ethnizität und Körper in Christian Petzolds "Jerichow" (2008) und Visar Morinas "Exil" (2020) - Morrien, Rita (Interkulturelle Konstellationen in Literaturwissenschaft und Literaturdidaktik. Festschrift für Michael Hofmann)

Droste Lab - Geschlecht #2 - Morrien, Rita; Gfrereis, Heike; Seifert, Nicole (Mit den Gespenstern leben. (Haunting/Heritage))

Transatlantisches Nachwirken - Annette von Droste-Hülshoff und Cindy Sherman im 'Cross-Mapping'-Verfahren - Morrien, Rita (Droste Jahrbuch 14)

Aquatische Relektüre: Christian Petzolds "Undine" erklärt Berlin und geht - Morrien, Rita (Weimarer Beiträge)

Wissenschaftsbezogener Rechtspopulismus/-extremismus an Hochschulen – Perspektiven von Betroffenen - Haker, Christoph; Otterspeer, Lukas (ZRex – Zeitschrift für Rechtsextremismusforschung)
Mit dem Begriff wissenschaftsbezogener Rechtspopulismus/-extremismus fokussiert der Beitrag solche (extrem) rechten Organisationen, Praktiken und Diskursstrategien, die sich auf das Feld der Wissenschaft beziehen. Dabei rückt in einer qualitativen Interview-Studie die Betroffenenperspektive in den Mittelpunkt, die ein blinder Fleck der Forschung ist: Wie nehmen Betroffene wissenschaftsbezogenen Rechtspopulismus/-extremismus wahr und welche Umgangsweisen finden sie? Präsentiert werden Ergebnisse zur widersprüchlichen Erscheinungsform von wissenschaftsbezogenem Rechtspopulismus/-extremismus. Neben erwartbaren Phänomenen (zum Beispiel (kultur-)rassistischen, misogynen, antidemokratischen und verschwörungstheoretischen Positionierungen) zeigt sich dieser insofern widersprüchlich, als dass er zwischen Inanspruchnahme von Wissenschaftlichkeit sowie Wissenschaftsfreiheit auf der einen Seite und Wissenschaftsfeindlichkeit auf der anderen Seite oszilliert. Er trifft mit Hochschulen auf Institutionen, deren Strukturen einen kritischen Umgang erschweren, und er wirkt weit über die jeweils konkreten Situationen seines Erscheinens hinaus. Unsere Analysen untermauern die Notwendigkeit, die Bedeutung von wissenschaftsbezogenem Rechtspopulismus/-extremismus in seiner Widersprüchlichkeit über die jeweiligen Situationen hinaus zu erkennen und wissenschaftsspezifische Antworten zu finden, die dieser Widersprüchlichkeit Rechnung tragen – und sind damit eine Aufforderung an Hochschulen und alle dort tätigen Personen.

Invariant Ruelle Distributions on Convex-Cocompact Hyperbolic Surfaces -- A Numerical Algorithm via Weighted Zeta Functions - Schütte, Philipp; Weich, Tobias (arXiv:2308.13463)
We present a numerical algorithm for the computation of invariant Ruelle distributions on convex co-compact hyperbolic surfaces. This is achieved by exploiting the connection between invariant Ruelle distributions and residues of meromorphically continued weighted zeta functions established by the authors together with Barkhofen (2021). To make this applicable for numerics we express the weighted zeta as the logarithmic derivative of a suitable parameter dependent Fredholm determinant similar to Borthwick (2014). As an additional difficulty our transfer operator has to include a contracting direction which we account for with techniques developed by Rugh (1992). We achieve a further improvement in convergence speed for our algorithm in the case of surfaces with additional symmetries by proving and applying a symmetry reduction of weighted zeta functions.

Editorial: Bildungsbezogener Rechtspopulismus/-extremismus - Haker, Christoph; Otterspeer, Lukas; Rödel, Severin Sales (ZSE Zeitschrift für Soziologie der Erziehung und Sozialisation)

Einladung zum Draußen-Bleiben. Safer Spaces sind nicht nur Schutzraum, sie sind eine Methode der Herrschafts- und Erkenntniskritik. - Haker, Christoph; Otterspeer, Lukas; Thole, Werner